Changing Performance Traditions and Bedouin Identity in the North Badiya, Jordan. - Hood, Kathleen; Al-Oun, Mohammad (Nomadic Peoples, 2014)
Although performance traditions have long been important parts of Bedouin identity in the North Badiya, Jordan, many factors have affected these traditions over the years, especially since the latter part of the twentieth century, resulting in the loss of some genres and the retention of others. This study examines how the traditions that remain, particularly poetry that is spoken or sung to the accompaniment of the rababa, are traditions from the male and public spheres, while the traditions that have been abandoned are those from the female and private spheres. Because of the separation of male/public and female/private realms, the male genres are the only ones that can be seen by outsiders, and thus are selected to be the public face of Bedouin identity.